IGV-001 cellular immunotherapy for newly diagnosed glioblastoma: overcoming the logistic challenge - Wong, Eric T.; Cielo, Deus; Svokos, Konstantina; Doberstein, Curt; Sampath, Prakash; Donahue, John E.; Punsoni, Michael; Rodrigues, Nuno; Rothell, Francesca; Edwards, Robert; Wang, Elaina; Riccelli, Tori; et al. (Frontiers in Oncology, 2025)
BackgroundIGV-001 is a type of cellular immunotherapy currently being investigated for treating glioblastoma (NCT04485949). It uses the patient’s tumor to elicit an autologous immune response.MethodsThe process involves (i) craniotomy for maximum safe resection of the glioblastoma, (ii) ex-vivo treatment of the tumor with an anti-sense oligodeoxynucleotide against insulin-like growth factor 1 receptor followed by irradiation, (iii) placement of the treated tumor in multiple bio-diffusion chambers, which are implanted into the patient’s abdominal sheath to elicit an immune response, and (iv) explantation of the chambers 48 hours later. The clinical trial was open at 32 sites in the United States, and eligible subjects were randomized in a 2:1 ratio to receive bio-diffusion chambers containing either conditioned glioblastoma tissue or a placebo. Patients subsequently proceeded to standard-of-care treatment with concomitant radiation-temozolomide, followed by 6 cycles of adjuvant temozolomide.ResultsThe execution of the IGV-001 protocol procedure is complicated and involves a multi-step process requiring mobilization of multiple services within the cancer center of a tertiary care hospital, including neurosurgery, neuro-oncology, radiation oncology, neuroradiology, cancer clinical trial office, and operating room personnel to fulfill the pre-specified protocol requirements in a timely fashion.ConclusionsWe have learned a great deal in the process of developing and executing our internal procedures for this clinical trial. Our description of the IGV-001 protocol workflow may serve as a “blueprint” for future implementation of this type of cellular immunotherapy at other centers. We further discuss some of the lessons we have learned during the trial.